Perencanaan Sumber Daya Manusia dalam Pendidikan Islam Menurut Kajian Manajemen Pendidikan Islam - Gusniati, Dina; Gusmira, Yessy; Jamilus, Jamilus (EDUTECH, 2025)
Human resource planning in Islamic education plays a crucial role in ensuring the availability of qualified educational personnel who possess strong competence, integrity, and adherence to Islamic values. This study aims to describe the definition of human resource planning in Islamic educational institutions, identify its strategic objectives, explain the systematic planning process, and present relevant planning models that can be applied effectively. This research employs a literature review method by examining various theoretical and empirical sources related to Islamic educational human resource management and modern HR principles. The results indicate that human resource planning does not only concern quantitative labor fulfillment, but also emphasizes the improvement of pedagogical competence, Islamic character, and adaptability to technological development and changing educational demands. Moreover, Islamic educational institutions must integrate competency-based, performance-based, data driven, and needs-based approaches with spiritual principles in order to achieve organizational sustainability. This study concludes that a comprehensive HR planning strategy will support the transformation of Islamic education to remain high-quality, competitive, and globally relevant.